Pemanfaatan Sarana Dan Prasarana Untuk Mendukung Diversitas Siswa Pada Sekolah Inklusi - Bella Karmelia; Anisatul Khoiriyah; Anggraini Anggraini; Hendri Marhadi (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Inclusive education requires facilities and infrastructure that support student diversity to ensure equal access to education for all. This research uses qualitative research with a case study research design. Qualitative research with a case study design is a form of qualitative research based on human understanding and behavior. This research uses data collection techniques using interviews, observation and documentation. The research results show that adequate facilities and infrastructure can create a safe, comfortable and conducive learning environment, can improve the quality of learning and develop various skills for student service in inclusive schools. This aims to support the development of each individual to create education that embraces student diversity.